2004
DOI: 10.1029/2003jd003680
|View full text |Cite
|
Sign up to set email alerts
|

Permafrost dynamics in the 20th and 21st centuries along the East Siberian transect

Abstract: The East Siberian transect, which has been designated by the International Geosphere‐Biosphere Program (IGBP) as its Far East transect, has unique permafrost conditions. Not only does permafrost underlie the entire transect, but also about one third of the region is underlain by an “ice complex,” consisting of extremely ice‐rich Late Pleistocene sediments. Given the possibility of a predicted future increase in global temperatures, an evaluation of the magnitude of changes in the ground thermal regime becomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 23 publications
(26 reference statements)
2
74
0
Order By: Relevance
“…Though some discussion still exists (Delisle, 2007) comparable results have been recently reported for various permafrost areas which add up to a wealth of existing research (see Nelson, 1996, 1997;Malevsky-Malevich et al, 2001;Nelson and Anisimov, 1993;Lawrence and Slater, 2005, and references therein): for instance Sazonova and Romanovsky (2004) use boundary conditions from climate change simulations with six GCMs and estimate for the East Siberian transect increases in the thickness of the active layer of 0.5 to 2 m on average as well as temperature increments of 2 to 6 • by the end of the 21st century; Stendel et al (2007) coincide on their results when analysing outputs of the GIPL permafrost model driven by boundary condi-tions provided in a donwscaling exercise for Eastern Siberia using the HIRHAM RCM driven by the ECHAM4-OPYC3 GCM outputs in the A2 and B2 scenarios; Cheng and Wu (2007) estimate future permafrost sinking for the QinghaiTibet Plateau by the end of the century. Also, using a climate change detection approach, Isaksen et al (2007) report extreme near-surface permafrost warming in [2005][2006] in Svalbard that is found to be compatible with estimated warming scenarios for the late 21st Century.…”
Section: Some Comments About Estimations Of Future Climate Changementioning
confidence: 89%
See 2 more Smart Citations
“…Though some discussion still exists (Delisle, 2007) comparable results have been recently reported for various permafrost areas which add up to a wealth of existing research (see Nelson, 1996, 1997;Malevsky-Malevich et al, 2001;Nelson and Anisimov, 1993;Lawrence and Slater, 2005, and references therein): for instance Sazonova and Romanovsky (2004) use boundary conditions from climate change simulations with six GCMs and estimate for the East Siberian transect increases in the thickness of the active layer of 0.5 to 2 m on average as well as temperature increments of 2 to 6 • by the end of the 21st century; Stendel et al (2007) coincide on their results when analysing outputs of the GIPL permafrost model driven by boundary condi-tions provided in a donwscaling exercise for Eastern Siberia using the HIRHAM RCM driven by the ECHAM4-OPYC3 GCM outputs in the A2 and B2 scenarios; Cheng and Wu (2007) estimate future permafrost sinking for the QinghaiTibet Plateau by the end of the century. Also, using a climate change detection approach, Isaksen et al (2007) report extreme near-surface permafrost warming in [2005][2006] in Svalbard that is found to be compatible with estimated warming scenarios for the late 21st Century.…”
Section: Some Comments About Estimations Of Future Climate Changementioning
confidence: 89%
“…This is due to the general inability of the forcing GCMs to reproduce permafrost and to the fact that this task is ultimately accomplished by the off-line land surface model or the nested regional model; also, often other permafrost related variables are diagnosed and compared to observations for validation like the thickness of the active later, permafrost area, freezing and thawing indices, snow cover, etc. (Malevsky-Malevich et al, 2001;Sazonova and Romanovsky, 2004). Some interesting case studies exist though that describe comparisons of simulated and observed soil temperatures in the process of their validation assessments.…”
Section: A Glimpse At the Surface Geothermal Climatementioning
confidence: 99%
See 1 more Smart Citation
“…An estimation based on the sampled cores and the landform classification shows that with an overall deepening of the active layer of 10 cm 700 000 t C (1.6 kg C m −2 ) will thaw out in both study areas combined (Table 5). A regional study of Siberian permafrost dynamics (Sazonova et al, 2004) includes scenarios where the active layer deepens by more than 100 cm in north-eastern Siberia at the end of the 21st century. This would result in an additional pool of available SOC of 5 830 000 t (13.2 kg C m −2 ) in the two study areas combined.…”
Section: The Fate Of Organic Carbon In Thermokarst-affected Yedoma Inmentioning
confidence: 99%
“…Permafrost regions, which cover about 24% of the Northern Hemisphere land surface (Zhang et al, 1999), are considered highly sensitive to climate change (e.g. Nelson et al, 2002;Sazonova et al, 2004). In this context, the monitoring of arctic permafrost landscapes is an important challenge; we must understand the present in order to quantify future environmental changes and their impacts in the Arctic.…”
Section: Introductionmentioning
confidence: 99%